Answer

Step by step solution by experts to help you in doubt clearance & scoring excellent marks in exams.

Updated On: 25-9-2020

Apne doubts clear karein ab Whatsapp par bhi. Try it now.

CLICK HERE

Loading DoubtNut Solution for you

Watch 1000+ concepts & tricky questions explained!

52.5 K+

2.6 K+

Text Solution

Answer :

N/aSolution :

In the expansion of `(3-(x^(3))/(6))^(7)` <br> No. of terms `=7+1=8`(even) <br> So. Here will be two middle terms . <br> Middle terms`=(8)/(2)`th term and `((8)/(2)+1)`th term <br> =4th term and 5th term <br> `T_(4)=T_(3+1)` <br> `=^(7)C_(3)(3)^(7-3).(-(x^(3))/(6))^(3)` <br> `=35 xx 81 xx ((-x^(9)))/(216)=(-105)/(8).x^(9)` <br> `" and " T_(5)=T_(4+1)` <br> `=^(7)C_(4)(3)^(7-4).((-x^(3))/(6))^(4)` <br> `=(35xx27xx x^(12))/(1296) =(35x^(12))/(48)`Image Solution

Find answer in image to clear your doubt instantly: